Leg- and joint stiffness in male elite high jump: the influence of stiffness on sports performance - Boden, E.; Braunstein, B.; Heinrich, K.; Sanno, M.; Stäudle, B.; Ritzdorf, W.; Brüggemann, G. P.; Albracht, K.; Goldmann, J.-P. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to analyse stiffness in the mechanical system of the world`s elite high jumpers. Seven male elite high jump athletes (personal best 2.24 m ± 0.06 m) were filmed with 19 Infrared-High-Speed-Cameras during jumping. Kinetics were captured with a force plate. It was found that a different leg and joint stiffness during takeoff enables nearly the same jumping height. For example, a typical power jumper with a leg stiffness of 543.6 N m-1 kg-1 reached 2.13 m, while a typical speed jumper with a leg stiffness of 1133.5 N m-1 kg-1 reached a comparable height of 2.12 m. Therefore, it seems that sports performance in single leg jumping is not limited by athlete`s leg and joint stiffness in a small group of male elite high jumpers.